Adenosine deaminase cutoff value when diagnosing tuberculous pleurisy in patients aged 40 years and older - Burcu Arpinar Yigitbas; Celal Satici; A. Filiz Kosar (The Clinical Respiratory Journal, 2021)
Abstract Introduction Tuberculous pleurisy (TBP) is one of the most common manifestations of extra‐pulmonary tuberculosis. In patients aged ≥40 years, a closed needle pleural biopsy is recommended with an adenosine deaminase (ADA) level of 40‐70 U/L. We aim to investigate whether the cutoff value of ADA and the cancer ratio in patients with TBP aged ≥40 years is different and determine the effects of both compounded biomarkers on diagnosing TBP. Materials and Methods Between 2009 and 2016, the ADA levels were measured in pleural effusions from patients who were admitted to the Chest disease clinic. Results Of the 196 patients included in the study, 104 were aged ≥40 years. A significant relationship was found between the serum LDH/pleural ADA (sLDH/pADA) ratio and ADA levels in patients aged >40 years (OR: 0.935 and OR: 1.085, respectively). The model using an ADA value ≥30 and an sLDH/pADA ratio <16 yielded a sensitivity of 94.25% (95% CI, 87.1‐98.10) in all patients and 69.23% (95% CI, 54.9‐81.28) in patients aged >40 years. Conclusion ADA and the sLDH/pADA ratio are simple, cost‐efficient, and obtain fast results and, therefore, are the preferred methods in TBP diagnosis. The diagnosis rate in the present study was 91% using ADA levels in combination with the sLDH/pADA ratio, both of which can be obtained only through thoracentesis.